2023
DOI: 10.1093/bjsopen/zrac158
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence, repair rate, and morbidity of groin hernias in Sierra Leone: cross-sectional household study

Abstract: Background Knowledge about the prevalence of groin hernias in sub-Saharan Africa is limited. Previous studies have demonstrated a higher incidence of the condition than the annual repair rate. This study aimed to investigate prevalence, incidence, annual repair rate, morbidity, and health-seeking behaviour of persons with groin hernias in Sierra Leone. Methods This population-based, cross-sectional household survey on groin h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This is much lower than the 13.1% recurrence rate that was identified from a nation-wide population study from Sierra Leone. However, most of those surgeries were done without mesh and with a longer follow-up time [ 2 ]. A previous study in Ghana demonstrated a recurrence rate of 1.8% after one year when the procedures were performed by general surgeons and MDs [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is much lower than the 13.1% recurrence rate that was identified from a nation-wide population study from Sierra Leone. However, most of those surgeries were done without mesh and with a longer follow-up time [ 2 ]. A previous study in Ghana demonstrated a recurrence rate of 1.8% after one year when the procedures were performed by general surgeons and MDs [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Sub-Saharan Africa, the estimated need for inguinal hernia repair is 204 to 210 per 100,000 population [1]. In Ghana, the estimated annual incidence of symptomatic inguinal hernia is 210 per 100,000 population, and a study from Sierra Leone has documented a prevalence of untreated groin hernia at 2.5% [2,3]. Although inguinal hernia repair is among the most common surgical procedures performed, accounting for up to 16.0% of all surgeries in Sierra Leone, the met need remains low [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hernia repair surgery impacts over 20 million people worldwide yearly [ 1 ]. Surgical site infection (SSI) remains one of the biggest challenges within the hernia repair field, leading to increase in morbidity, mortality and costs [ 2 ].…”
Section: Introductionmentioning
confidence: 99%